Enhancing conformational flexibility of dendronized triphenylene via diethylene glycol linkers lowers transitions of helical columnar, Frank-Kasper, and quasicrystal phases. (June 2022) - Imam, Mohammad R.; Peterca, Mihai; Xiao, Qi; Percec, Virgil
Highlights: ● Dendronized triphenylenes self-organize via a crown conformation. ● Diethylene glycol linkers decrease transition temperatures by increasing flexibility. ● Spherical helices are distorted short fragments of helical columns. ● Columnar, Frank-Kasper and quasicrystal phases are stabilized by identical principles. ● Extended supramolecular backbones stabilize supramolecular dendrimer assemblies. Abstract: A library of triphenylene (Tp) dendronized with self-assembling dendrons via a diethylene glycol linker was synthesized and the corresponding self-organizations were analyzed. They self-organize via a crown conformation in helical columns and spherical helices that produce hexagonal columnar, Frank-Kasper and soft quasicrystal assemblies. The same self-organizations are produced in the absence of the diethylene glycol linker except that the phase transitions and isotropization temperatures occur at lower temperatures in the presence of the linker. The incorporation of the flexible diethylene glycol linker induces also strong π-π stacking in helical columns. Spherical helices are spherical distorted short fragments of helical columns and therefore the same principles determine the thermal stability of the hexagonal columnar and of Frank-Kasper and quasicrystal assemblies except that the length of the supramolecular backbone is much longer in helical columns. A comparison of these systems with side-chain liquid crystals indicates that supramolecular dendrimers are stabilized by extended supramolecular backbone conformations. This result suggests pathways to molecularly engineer phase transitions of supramolecular dendrimers self-organized from crown conformations. Graphical abstract: Image, graphical abstract